It’s Lovely at the Top: Hierarchical Levels, Identities, and Perceptions of Organizational Ethics - Treviño, Linda Klebe (Business ethics quarterly, 2008)
Senior managers are important to the successful management of ethics in organizations. Therefore, their perceptions of organizational ethics are important. In this study, we propose that senior managers are likely to have a more positive perception of organizational ethics than lower level employees do largely because of their managerial role and their corresponding identification with the organization and need to protect the organization’s image as well as their own identity. By contrast, lower level employees are more likely to be cynical about the organization’s ethics. In order to compare senior managers’ and lower level employees’ perceptions of ethics in the organization, we surveyed randomly selected senior managers and lower level employees in three firms. We found that perceptions of ethics in the organization differed predictably across levels, with senior managers’ perceptions being significantly more positive and lower level employees’ perceptions being more negative. Implications for practice and research are discussed.